2017
DOI: 10.1002/jbm.a.35985
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic calcium phosphate/polyelectrolyte multilayer coatings for sequential delivery of multiple biological factors

Abstract: Combinations of growth factors synergistically enhance tissue regeneration, but typically require sequential, rather than co-delivery from biomaterials for maximum efficacy. Polyelectrolyte multilayer (PEM) coatings can deliver multiple factors without loss of activity; however, sequential delivery from PEM has been limited due to interlayer diffusion that results in co-delivery of the factors. This study shows that addition of a biomimetic calcium phosphate (bCaP) barrier layer to a PEM coating effectively pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…The bCaP deposition procedure followed a previously reported method [ 21 , 37 ]. All of the reagents were used as received from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bCaP deposition procedure followed a previously reported method [ 21 , 37 ]. All of the reagents were used as received from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Systems of particular value are those that deliver the molecules in a highly localized manner, because that reduces the off target effects of the potent molecules being delivered [ 19 ]. The combined use of a biomimetic calcium phosphate (bCaP) barrier layer with a poly- l -Lysine (PLLys) and poly- l -Glutamic acid (PLGlut) polyelectrolyte multilayer (PEM) is one of the few systems capable of non-overlapping and the sequential delivery of two factors [ 20 , 21 ]. PEM coatings are generated by layer-by-layer assembly involving deposition of the polyelectrolyte molecules on a surface by many different techniques, including dipping into alternate solutions of differently charged molecules [ 17 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…) . Lysine has been widely used in biomaterials and studies have revealed its antibacterial properties and biofilm‐disrupting activity . When incorporated in the adhesive formulation, this essential amino acid could buffer the interfacial micro‐environment without leaching amine‐containing cytotoxic species.…”
Section: Strategies For Adhesive/dentin Interfacial Integritymentioning
confidence: 99%
“…Lysine, an essential amino acid, has been widely reported as an important component in biomaterials because of its biocompatibility [1820]. Its lipophilic derivatives, lysine-based small molecules, showed commendable broad-spectrum antibacterial activity and biofilm-disrupting activity [21].…”
Section: Introductionmentioning
confidence: 99%